2014
DOI: 10.1155/2014/728762
|View full text |Cite
|
Sign up to set email alerts
|

The Trajectory and the Related Physical and Social Determinants of Body Mass Index in Elementary School Children: Results from the Child and Adolescent Behaviors in Long-Term Evolution Study

Abstract: This study explored developmental trajectory patterns of BMI and associated factors. Participants included 1,609 students who were followed from age 7 to 12 years. Data collection involved annual self-administered questionnaires and records of height and weight. An ecological model was used to identify the factors associated with BMI trajectories. Group-based trajectory models and multinomial logit models were used in the statistical analysis. There were gender differences in BMI trajectories. Among boys, four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(34 citation statements)
references
References 29 publications
3
29
2
Order By: Relevance
“…The remaining 2 studies for screen time ) and TV viewing (Creighton et al 2011;Drenowatz et al 2013), and 1 study for computer use (Magee et al 2013) reported null findings. Among 9 of the studies, significant associations with body composition were not observed across all age groups (Hands et al 2011), sex groups (Altenburg et al 2012;Barnett et al 2010;Falbe et al 2013;Lin et al 2014), exposure measures (e.g., TV vs. movie) (Falbe et al 2013;Gilbert-Diamond et al 2014), or measures of body composition (Altenburg et al 2012;Grontved et al 2014). Primarily null findings were observed for accelerometer-derived sedentary time and breaks as well as video games and total sedentary behaviour with body composition.…”
Section: Body Compositionmentioning
confidence: 94%
See 3 more Smart Citations
“…The remaining 2 studies for screen time ) and TV viewing (Creighton et al 2011;Drenowatz et al 2013), and 1 study for computer use (Magee et al 2013) reported null findings. Among 9 of the studies, significant associations with body composition were not observed across all age groups (Hands et al 2011), sex groups (Altenburg et al 2012;Barnett et al 2010;Falbe et al 2013;Lin et al 2014), exposure measures (e.g., TV vs. movie) (Falbe et al 2013;Gilbert-Diamond et al 2014), or measures of body composition (Altenburg et al 2012;Grontved et al 2014). Primarily null findings were observed for accelerometer-derived sedentary time and breaks as well as video games and total sedentary behaviour with body composition.…”
Section: Body Compositionmentioning
confidence: 94%
“…c Dose-response gradient was observed for higher TV, sedentary time, screen time, computer with unfavourable body composition in 14 studies (Barnett et al 2010;Miller 2011;Altenburg et al 2012;Basterfield et al 2012b;Dumith et al 2012;Veitch et al 2012;Falbe et al 2013;Magee et al 2013;Mitchell et al 2013aMitchell et al , 2013bWilliams et al 2013;Berentzen et al 2014;Grontved et al 2014;Lin et al 2014).…”
Section: ) Long Accelerometer-derived Sedentary Bouts (≥5 Min)mentioning
confidence: 99%
See 2 more Smart Citations
“…Obese children are at increased risk of becoming obese adults and of developing chronic diseases (type 2 diabetes and cardiovascular diseases) [1]. The preschool age is an important period for adopting healthy lifestyle behaviours including eating and physical activity habits [2].…”
Section: Introductionmentioning
confidence: 99%